2016
DOI: 10.15407/microbiolj78.06.019
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Weed Phytopathogens in Wheat Agrophytocenosis

Abstract: Bacterial diseases, pests and weeds are the main factors that do not allow generating high yields of agricultural crops. The article presents the results of a study of agents of weed diseases. It was shown that the affected weeds in wheat agrophytocenosis present an ecological niche for phytopathogenic bacteria, belonging to the species Pseudomonas syringae, Pseudomonas viridiflava, Pseudomonas fluorescens, Pectobacterium carotovorum, Pantoea agglomerans, Xanthomonas translucens and Pseudomonas sp. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The contribution of P. syringae to crop loss is not well understood and therefore remains largely underestimated. It has been shown that grain infestation, as well as affected weeds in wheat agrophytocenoses are very important in the epidemiology of the disease (Pasichnyk, 2016;Umesha, 2020). Isolates of P. syringae are taxonomically divided into pathovars, based substantially on their host.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of P. syringae to crop loss is not well understood and therefore remains largely underestimated. It has been shown that grain infestation, as well as affected weeds in wheat agrophytocenoses are very important in the epidemiology of the disease (Pasichnyk, 2016;Umesha, 2020). Isolates of P. syringae are taxonomically divided into pathovars, based substantially on their host.…”
Section: Introductionmentioning
confidence: 99%